The People of Bais City: Selected Social Dimensions - Abregana, Betty C. (Silliman Journal, 2023)
This paper has two parts: the first section presents some physical and social characteristics of Bais City taken from available reports; the second part presents primary data taken from interviews conducted in 1989 in three coastal barangays.